A Report of Multiple Sclerosis Registry in Mazandaran Province 2019-2021 - Seyed Mohammad Baghbanian; Abolfazl Hosseinnataj; Sharaeh Eskandarieh; Mohammadali Sahraian (Journal of Mazandaran University of Medical Sciences, 2022)
Background and purpose: Multiple sclerosis (MS) is a chronic inflammatory and neurodegenerative disease of the central nervous system. The purpose of this study was to report the information of MS patients registered in Mazandaran MS Registry System between 2019 and 2021. Materials and methods: This retrospective study was performed in patients with MS living in Mazandaran province using the MS national registry system in Iran. Results: A total of 2211 patients were found, including 72.8% females and the mean age of patients was 36.97±9.47 years. Most of the patients had Relapsing remitting (RR) MS (61.2%) followed by Secondary progressive (SP) MS (19.6%) and a family history of the disease was seen in 16.2%. Most of the patients lived in populated cities; Sari and Amol. Interferons, Rituximab, and Fingolimod were found to be the most widely used drugs. The mean score for Expanded Disability Status Scale (EDSS) was higher in men than women. The mean EDSS scores were the lowest in clinically isolated syndrome (CIS) type of the disease and the highest in the SP and RP types. The level of disability was significantly higher in men than women (P<0.001). Conclusion: The types of MS in Mazandaran province is similar to global data of this disease, but the increasing prevalence of familial MS in this province compared with other provinces requires more detailed studies.